ANALISIS KINERJA BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DALAM PELAKSANAAN KENAIKAN PANGKAT PEGAWAI NEGERI SIPIL DI WILAYAH KABUPATEN MAHAKAM ULU - Nanik Pujiastuti dan Mulyanah (Prodi Ilmu Administrasi Negara, 2020)
The promotion in the Mahakam Ulu District Government even though it has been implemented in the area still seems to use bureaucratic tortuous and policies that make it difficult for Civil Servants to be promoted. The problems in this research is how the implementation of promotion and inhibition factors promotion through the adjustment of diploma in the Government of Mahakam Ulu Regency. Research Objective to know the process of implementation of promotion of Civil Servant for those who get a diploma in Government of Mahakam Ulu Regency. In order to research for the development of theory and concepts as well as inputs to related institutions regarding the promotion of the rank of Civil Servant who btained a diploma. The approach used is normative through literature and empirical study through direct field research and also free guided interviews to the authorities related to research to complement the existing data. The increase of the rank of civil servant in Mahakam Ulu District Government has a role in its duty and function to conduct the process of appointment promotion through diploma for Civil Servant which is within the Government of Mahakam Ulu Regency, whose administrative process is done by Regional Personnel Board of Mahakam Ulu Regency